Effect of surface anodizing on the bonding properties of aluminum alloy/glass-fiber reinforced polypropylene random copolymer hybrid joints. (April 2023) - Chen, Jing; Huang, Jin; Wu, Yutao; Du, Kunpeng; Xiang, Hongxia; Li, Youbing; Yang, Chaolong; Xia, Xiaochao
Abstract: Polymer-metal hybrid (PMH) joints of glass-fiber reinforced polypropylene random copolymer (GFRPPR) and aluminum alloy were prepared by the self-made hot pressing technology (HPT). The PPR copolymer was grafted with maleic anhydride and reinforced with 30% short glass fiber, and the aluminum alloy surface was anodized in oxalic acid and phosphoric acid solution, respectively. The PMH interfaces were mainly characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), X-ray photoelectron spectroscopy (XPS) and contact angle tests. Anodized in the phosphoric acid solution, the anodized aluminum alloy surface showed needle-shaped honeycomb-like microstructures. The phosphoric acid anodized aluminum alloy surface was beneficial for polymer melt to flow into and form interlocking microstructures due to its micro porous structure, and the corresponding tensile shear strength and work of fracture reached up to 10.88 MPa and 16.15 kJ m −2, respectively.